Telehealth, Data Privacy, and Cybersecurity and Their Implications for STEM Education - Triplett, William J.; El Islami, R. Ahmad Zaky (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This article examined the factors of telehealth, data privacy, and cybersecurity in today’s healthcare environment and discusses what key issues should be addressed and what effective solutions should be implemented and their implications for STEM Education. As telehealth brings more opportunities for the delivery of care, patient data have emerged as critical areas of concern. This paper aimed at discussing the telehealth data privacy concerns, the current and future cybersecurity threats facing healthcare systems, and recommended ways of enhancing these two areas. Based on a literature analysis and interviews with telehealth experts, this paper identifies that telehealth has unique advantages and opens specific security threats. The studies demonstrate the importance of enhanced data security policies, better IT systems to prevent unauthorized access, and constantly evolving legislation to safeguard the patient’s life and their personal information. The implications of telehealth, data privacy, and cybersecurity for STEM Education are these three contexts can be used as the contexts in the science learning process.